The Sea, the Atreids, Hospitality: A Setting for Odysseus - de Holanda, Luisa Severo Buarque (Revista Archai, 2026)
Based on the assumption that the Odyssey, as a narrative of return, is a poem that praises the heroic ability to stay alive, this article will explore the setting in which the poem takes place, from the point of view of the threats that befall Odysseus and which he must evade. In this sense, our proposal is to analyse three elements, growing in importance, which contribute to the formation of a panorama of suspense, adventure and risk for the hero, namely: the sea, the role that the Atreids’ saga plays in the plot and the practice of hospitality as a rule to be followed to mitigate risks, but which is frequently broken throughout the poem.